Influences of Microbial Infections on Hormonal Balance - Hazim Salih , Wafaa; S. H. Al-Khalidy , Huda (Hammurabi Journal of Medical Sciences, 2025)
Although considerable knowledge exists on bacterial infections' ability to alter the immune response, significantly less is understood about their impact on hormonal regulation, specifically concerning the stress hormone cortisol. Cortisol is a vital hormone in an organism's stress response, its levels are precisely controlled by hypothalamic-pituitary-adrenal axis. It is triggered during bacterial infections, leading to disrupted cortisol secretion, which impairs the body's innate reaction to stress, both acute and chronic. This review elucidates the mechanisms by which bacterial infections affect cortisol levels, beginning with the disruption of normal cortisol production due to acute or chronic infection. Cortisol serves a dual function in regulating the immune response: it functions as an inflammation reducing agent, while its dysregulation frequently results in heightened inflammatory damage. The significant implications of alterations in cortisol levels for stress-related disorders, including anxiety and depression, as well as cardiovascular diseases, have been examined. It also examines the influence of several bacterial pathogens on cortisol modulation, indicating that distinct infections may elicit divergent responses in cortisol dynamics. A comprehensive understanding of the interplay between bacterial infections and cortisol regulation will yield significant insights into stress management, immunological responses, and potential therapeutic targets.